2018
DOI: 10.1016/j.redox.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Sirtuin 3 on ameliorating nonalcoholic fatty liver disease: The role of the ERK-CREB pathway and Bnip3-mediated mitophagy

Abstract: Increased mitochondrial damage is related to the progression of a diet-induced nonalcoholic fatty liver disease. The aim of our study is to investigate the role of Sirtuin 3 (Sirt3) in treating nonalcoholic fatty liver disease with a focus on mitophagy and the ERK-CREB pathway. Our data indicated that Sirt3 was downregulated in liver tissue in response to chronic HFD treatment. Interestingly, re-introduction of Sirt3 protected hepatic function, attenuated liver fibrosis, alleviated the inflammatory response, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
215
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(220 citation statements)
references
References 75 publications
4
215
0
1
Order By: Relevance
“…The influence of mitochondrial stress on neuronal injury has been extensively explored. For example, in spinal cord injury, mitochondrial dysfunction is associated with neuronal apoptosis in a manner dependent on Akt‐GSK3β pathway . In hippocampal neuron development, mitochondrial dysfunction promotes chronic energy depletion due to iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of mitochondrial stress on neuronal injury has been extensively explored. For example, in spinal cord injury, mitochondrial dysfunction is associated with neuronal apoptosis in a manner dependent on Akt‐GSK3β pathway . In hippocampal neuron development, mitochondrial dysfunction promotes chronic energy depletion due to iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in spinal cord injury, mitochondrial dysfunction is associated with neuronal apoptosis in a manner dependent on Akt-GSK3β pathway. 67,68 In hippocampal neuron development, mitochondrial dysfunction promotes chronic energy depletion due to iron deficiency. Besides, attenuation of mitochondrial oxidative stress via antioxidant mitoQ improves RPS-mediated sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mitochondrial apoptosis has been acknowledged as the primary reason for reperfusion-mediated renal tubular epithelial cell apoptosis [53]. In addition, mitochondrial DNA damage [54], mitochondrial biosynthesis disorder [55], and mitophagy delay [56] have been found to be implicated in mitochondrial dysfunction and renal damage exerted by I/R injury. In the present study, we also found that mitochondria were the potential target of the renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…State 3 respiration was initiated by adding ADP (150 nmol/L); state 4 was measured as the rate of oxygen consumption after ADP phosphorylation. The respiratory control ratio (state 3/state 4) and the ADP/O ratio (number of nmol ADP phosphorylated to atoms of oxygen consumed) were calculated as previously described …”
Section: Methodsmentioning
confidence: 99%